Ketimpangan pendidikan dan pendapatan serta pengaruhnya terhadap pertumbuhan ekonomi di daerah tertinggal, terdepan dan terluar (3T) - Riyadi Riyadi; Diny Ghuzini (Jurnal Kependudukan Indonesia, 2021)
Inequality is one of the urgent issues, especially in the least developed, frontier, and outermost regions (3T) in Indonesia. This study aims to analyze education and income inequality and their effects on economic growth in the 3T regions in Indonesia. This study uses data from Susenas Kor and other publications by Statistics Indonesia in 2015-2017. The unit of analysis of this study is 142 districts/municipalities of the 3T regions. The results show that education inequality in the 3T regions can be categorized as a low inequality. In contrast, income inequality is classified as moderate inequality with a declining trend over the observation period. Education inequality is generally higher in rural areas and among the female population, while income inequality is higher in urban areas and among the male population. It is also shown that education inequality has a negative effect on economic growth, while income inequality has a positive effect on economic growth in the 3T regions. Policy recommendations that can be given are the provision of free formal and non-formal education and targeted education in remote areas. Regarding income inequality, the government should expand job opportunities, increase skills, and support micro, small and medium enterprises through training, business capital assistance and marketing assistance.